Aporte lipidico em dietas de juvenis do robalo, Centropomus parallelus, para um máximo de crescimento em cultivos com água estuarina - Pinto, Ricardo Camurça Correia (2011)
The present work aimed at evaluating the growth response of the fat snook, C. parallelus to the total lipid and gross energy content of the diet. Five isonitrogenous slow-sinking diets with 480 g/kg of crude protein were lab-extruded. Lipid content of the diets varied at 100, 120, 140, 160 and 180 g/kg with a corresponding gross energy level of 4,056, 4,157, 4,322, 4,499 and 4,696 kcal/kg. To start the study, hatchery-reared juveniles of 6.5 ± 2.4 g were stocked in 1,000 l round outdoor tanks under 10 fish/m3. Six replicate tanks were assigned for each tested diet. Snooks were fed three times daily to satiation by hand-broadcasting and reared for 96 days. Fish wet body weight was checked individually every 24 days of rearing. Over the rearing period, dissolved oxygen was kept above 90% saturation, while water salinity, pH and temperature reached 35 ± 2 ppt, 8.6 ± 0.2 and 30.7 ± 0.7°C, respectively. Ammonia, nitrite and nitrate nitrogen concentration increased significantly along the experiment, varying from 0.27 to 0.42, 0.020 to 0.103 and from 0.88 to 1.58 mg/l, respectively. At harvest, there was no statistical difference in fish performance among the different feeding treatments (P > 0.05, ANOVA). Fish reached 38.2 ± 12.5 g in body weight and gained 317 ± 40 g/m3 in biomass. Fish attained a specific grow rate of 1.92 ± 0.12% or 0.34 ± 0.04 g/day. No fish mortality was observed along the culture period. Mean final food conversion ratio reached 1.77 ± 0.25 with a protein retention ratio of 1.19 ± 0.17. There was a significant increase (P > 0.05, Tukey HSD) of the viscerosomatic (VSI) and visceral fat (VFI) indexes with an increase in the lipid content of the diets. No significant differences among feeding treatments in the hepatosomatic indexes. This indicated the highest fat accumulation in the visceral cavity of fish was due to a high fat input in the diets. By the broken-line regression analysis, the quantitative lipid and energy requirements of the fat snook was estimated at 122 g/kg and 4,216 kcal/kg, respectively. Results from the present work indicated that high lipid-content diets are not required in the rearing of juvenile fat snook, which displayed tolerance to confinement, disease resistance and ease to manage.